Model Checking and Artificial Intelligence 6th International Workshop, MoChArt 2010, Atlanta, GA, USA, July 11, 2010, Revised Selected and Invited Papers - Meyden, Ron.; Smaus, Jan-Georg.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book presents revised versions of selected papers from the 6th Workshop on Model Checking and Artificial Intelligence, MoChArt 2010, held in Atlanta, GA, USA in July 2010, as well as papers contributed subsequent to the workshop. The 7 papers presented were carefully reviewed and selected for inclusion in this book. In addition, the book also contains an extended abstract of the invited talk held at the workshop. The topics covered by these papers are general search algorithms, application of AI techniques to automated program verification, multiagent systems and epistemic logic, abstraction, epistemic model checking, and theory of model checking.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Programming Techniques; Software Engineering; Logics and Meanings of Programs; Mathematical Logic and Formal Languages